Exosome-Derived From Sepsis Patients' Blood Promoted Pyroptosis of Cardiomyocytes by Regulating miR-885-5p/HMBOX1 - Tu, Guo-wei; Ma, Jie-fei; Li, Jia-kun; Su, Ying; Luo, Jing-chao; Hao, Guang-wei; Luo, Ming-hao; Cao, Yi-rui; Zhang, Yi; Luo, Zhe (Frontiers in Cardiovascular Medicine, 2022)
Background: Septic myocardial depression has been associated with increased morbidity and mortality. miR-885-5p has been shown to regulate cell growth, senescence, and/or apoptosis. Published studies demonstrated that Homeobox-containing protein 1 (HMBOX1) inhibits inflammatory response, regulates cell autophagy and apoptosis. However, the role of miR-885-5p/HMBOX1 in sepsis and septic myocardial depression and the underlying mechanism is not fully understood. Materials and methods: Exosomes (exos) derived from sepsis patients (sepsis-exos) were isolated using ultracentrifugation. Rats were subjected to caecal ligation and puncture surgery and treated with sepsis-exos. HMBOX1 was knocked down or over-expressed in AC16 cells using lentiviral plasmids carrying short interfering RNAs targeting human HMBOX1 or carrying HMBOX1 cDNA. Cell pyroptosis was measured by flow cytometry. The secretion of IL-1β and IL-18 was examined by ELISA kits. Quantitative PCR or western blot was used for gene expression. Results: Sepsis-exos increased the level of miR-885-5p, decreased HMBOX1, elevated IL-1β and IL-18, and promoted pyroptosis in AC16 cells. Septic rats treated with sepsis-exos increased the serum inflammatory cytokines in associated with increased pyroptosis-related proteins of hearts. MiR-885-5p bound to the three prime untranslated region of HMBOX1 to negatively regulate its expression. Overexpressing HMBOX1 reversed miR-885-5p-induced elevation of inflammatory cytokines and up-regulation of NLRP3, caspase-1 and GSDMD-N in AC16 cells. Mechanistic study indicated that the effect of HMBOX1 was NF-κB dependent. Conclusion: Exosome-derived from sepsis patients promoted the pyroptosis of AC16 cells through miR-885-5p via HMBOX1. The results show the significance of miR-885-5p/HMBOX1 axis in myocardial cell pyroptosis and provide new directions for treatment of septic myocardial depression.